2008
DOI: 10.1038/embor.2008.112
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear transit of the RNA‐binding protein She2 is required for translational control of localized ASH1 mRNA

Abstract: Cytoplasmic localization and localized translation of messenger RNAs contribute to asymmetrical protein distribution. Recognition of localized mRNAs by RNA-binding proteins can occur in the cytoplasm or, alternatively, co-or post-transcriptionally in the nucleus. In budding yeast, mRNAs destined for localization are bound by the She2 protein before their nuclear export. Here, we show that a specific transcript, known as ASH1 mRNA, and She2 localize specifically to the nucleolus when their nuclear export is blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 33 publications
2
90
3
Order By: Relevance
“…A role of nuclear She2p in translational control is indeed supported by recent data from the Jansen lab, which showed that nuclear exclusion of She2p accelerates Ash1p synthesis (Du et al, 2008). Intriguingly, Du et al did not report any defect in ASH1 mRNA localization when She2p was excluded from the nucleus, unlike what we observed (see Figure 7).…”
Section: Nuclear She2p Couples Mrna Localization and Translational Recontrasting
confidence: 55%
See 3 more Smart Citations
“…A role of nuclear She2p in translational control is indeed supported by recent data from the Jansen lab, which showed that nuclear exclusion of She2p accelerates Ash1p synthesis (Du et al, 2008). Intriguingly, Du et al did not report any defect in ASH1 mRNA localization when She2p was excluded from the nucleus, unlike what we observed (see Figure 7).…”
Section: Nuclear She2p Couples Mrna Localization and Translational Recontrasting
confidence: 55%
“…Knockouts of these genes disrupt ASH1 mRNA localization and Ash1p sorting to the daughter cell Gu et al, 2004). She2p shuttles between the cytoplasm and the nucleus (Kruse et al, 2002), and recent evidence suggests that the nuclear transit of She2p is involved in the translational regulation of ASH1 mRNA (Du et al, 2008). However, the specific role of She2p in the nucleus is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other components, like She1p-5p, are essential for proper localization of ASH1 mRNA and Ash1p sorting (Long et al 1997). Interestingly, when the She2p NLS is mutated so that it can no longer enter the nucleus, it can still bind to the target mRNA on its own in the cytoplasm (Du et al 2008), but with a diffuse RNA phenotype rather than bud tip-anchored mRNA localization (Shen et al 2009). Furthermore, when the N terminus of She3p, an adapter of She2 interaction with Myo4p, was fused with She2p to prevent its nuclear import, ASH1 mRNAs could localize to the bud tip as in wild-type cells, but, remarkably, failed to redistribute Ash1p asymmetrically (Du et al 2008).…”
Section: Cotranscriptional Regulation Of Mrna Localizationmentioning
confidence: 99%